Impact of bacterial strain acquisition in the lung of patients with COPD: the AERIS study - Lucio Malvisi; Aparna Yarraguntla; Marie-Cécile Mortier; Karen Osman; David W. Cleary; Béatrice Sente; Thierry G. Pascal; Vincent Weynants; Stuart C. Clarke; Laura Taddei; Tom M. A. Wilkinson; Jeanne-Marie Devaster; et al. (Infectious Diseases, 2022)

Bringing the diversity of Planctomycetes into the light: Introduction to papers from the special issue on novel taxa of Planctomycetes - Damien P. Devos; Olga M. Lage; Iain C. Sutcliffe (Antonie van Leeuwenhoek, 2020)

Maioricimonas rarisocia gen. nov., sp. nov., a novel planctomycete isolated from marine sediments close to Mallorca Island - Elena Rivas-Marin; Sandra Wiegand; Nicolai Kallscheuer; Mareike Jogler; Stijn H. Peeters; Anja Heuer; Mike S. M. Jetten; Christian Boedeker; Manfred Rohde; Damien P. Devos; Christian Jogler (Antonie van Leeuwenhoek, 2020)
Planctomycetes are ubiquitous bacteria with environmental and biotechnological relevance. Axenic cultures of planctomycetal strains are the basis to analyse their unusual biology and largely uncharacterised metabolism in more detail. Here, we describe strain Mal4 T isolated from marine sediments close to Palma de Mallorca, Spain. Strain Mal4 T displays common planctomycetal features, such as division by polar budding and the presence of fimbriae and crateriform structures on the cell surface. Cell growth was observed at ranges of 10–39 °C (optimum at 31 °C) and pH 6.5–9.0 (optimum at 7.5). The novel strain shows as pear-shaped cells of 2.0 ± 0.2 × 1.4 ± 0.1 µm and is one of the rare examples of orange colony-forming Planctomycetes. Its genome has a size of 7.7 Mb with a G+C content of 63.4%. Phylogenetically, we conclude that strain Mal4 T (= DSM 100296 T = LMG 29133 T ) is the type strain representing the type species of a novel genus, for which we propose the name Maioricimonas rarisocia gen. nov., sp. nov.

Thalassoglobus polymorphus sp. nov., a novel Planctomycete isolated close to a public beach of Mallorca Island - Elena Rivas-Marin; Sandra Wiegand; Nicolai Kallscheuer; Mareike Jogler; Stijn H. Peeters; Anja Heuer; Mike S. M. Jetten; Christian Boedeker; Manfred Rohde; Damien P. Devos; Christian Jogler (Antonie van Leeuwenhoek, 2020)
Access to axenic cultures is crucial to extend the knowledge of the biology, lifestyle or metabolic capabilities of bacteria from different phyla. The phylum Planctomycetes is an excellent example since its members display an unusual cell biology and complex lifestyles. As a contribution to the current collection of axenic planctomycete cultures, here we describe strain Mal48 T isolated from phytoplankton material sampled at the coast of S’Arenal close to Palma de Mallorca (Spain). The isolated strain shows optimal growth at pH 7.0–7.5 and 30 °C and exhibits typical features of Planctomycetes. Cells of the strain are spherical to pear-shaped, divide by polar budding with daughter cells showing the same shape as the mother cell, tend to aggregate, display a stalk and produce matrix or fimbriae. Strain Mal48 T showed 95.8% 16S rRNA gene sequence similarity with the recently described Thalassoglobus neptunius KOR42 T . The genome sequence of the novel isolate has a size of 6,357,355 bp with a G+C content of 50.3%. A total of 4874 protein-coding genes, 41 tRNA genes and 2 copies of the 16S rRNA gene are encoded in the genome. Based on phylogenetic, morphological and physiological analyses, we conclude that strain Mal48 T (= DSM 100737 T = LMG 29019 T ) should be classified as the type strain of a new species in the genus Thalassoglobus , for which the name Thalassoglobus polymorphus sp. nov. is proposed.

Introduction to papers from the third meeting on the Planctomycetes-Verrucomicrobia-Chlamydiae bacteria: new model organisms in the omics era - Olga Maria Lage; Damien P. Devos (Antonie van Leeuwenhoek, 2018)

The Paradigms They Are a-Changin’: past, present and future of PVC bacteria research - Elena Rivas-Marín; Damien P. Devos (Antonie van Leeuwenhoek, 2018)

Towards the European eradication of the North American ruddy duck - P. A. Robertson; T. Adriaens; A. Caizergues; P. A. Cranswick; K. Devos; C. Gutiérrez-Expósito; I. Henderson; B. Hughes; A. C. Mill; G. C. Smith (Biological Invasions, 2015)

Mind the PVCs - Damien P. Devos; Naomi L. Ward (Environmental Microbiology, 2014)

Re-interpretation of the evidence for the PVC cell plan supports a Gram-negative origin - Damien P. Devos (Antonie van Leeuwenhoek, 2014)

The 1st EMBO workshop on PVC bacteria—Planctomycetes–Verrucomicrobia–Chlamydiae superphylum: Exceptions to the bacterial definition? - Damien P. Devos; Christian Jogler; John A. Fuerst (Antonie van Leeuwenhoek, 2013)

Impact of combination therapy with aminoglycosides on the outcome of ICU-acquired bacteraemias - P.-Y. Delannoy; N. Boussekey; P. Devos; S. Alfandari; C. Turbelin; A. Chiche; A. Meybeck; H. Georges; O. Leroy (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Adult community-acquired bacterial meningitis requiring ICU admission: epidemiological data, prognosis factors and adherence to IDSA guidelines - H. Georges; A. Chiche; S. Alfandari; P. Devos; N. Boussekey; O. Leroy (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Is HSP70 Involved in Acclimation to Cadmium in the Chinese Crab, Eriocheir sinensis ? - F. Silvestre; G. Trausch; P. Devos (Bulletin of Environmental Contamination and Toxicology, 2007)

Chromosome aberrations in wheat nullisomic-tetrasomic and ditelosomic lines - K. M. Devos; M. E. Sorrells; J. A. Anderson; T. E. Miller; S. M. Reader; A. J. Lukaszewski; J. Dubcovsky; P. J. Sharp; J. Faris; M. D. Gale (Cereal Research Communications, 1999)

Fifty new microsatellite loci for the wheat genetic map - P. Stephenson; G. Bryan; J. Kirby; A. Collins; K. Devos; C. Busso; M. Gale (Theoretical and Applied Genetics, 1998)

Historical Variations in Lead Fluxes in the Pyrenees (Northeast Spain) from a Dated Lake Sediment Core - L. Camarero; P. Masqué; W. Devos; I. Ani-Ragolta; J. Catalan; H.C. Moor; S. Pla; J.A. Sanchez-Cabeza (Water, Air, & Soil Pollution, 1998)

Effect of cadmium on the cytoskeleton and morphology of gill chloride cells in parr and smolt Atlantic salmon (Salmo salar) - E. Devos; P. Devos; M. Cornet (Fish Physiology and Biochemistry, 1998)